Monte Carlo Characterization of an Individual Albedo Neutron Monitor - Rosane Moreira Ribeiro; Denison Souza-Santos (Brazilian Journal of Radiation Sciences)
An individual albedo neutron dosimeter is simulated with the Geant4 toolkit. The simulation results are compared with results from an international intercomparison for Monte Carlo codes. The doses are obtained for thermoluminescent dosimeters irradiated free in the air and also on the surface of a water phantom for different neutron energy values. The Geant4 toolkit was not used by any of the participants in this intercomparison, so with these results we can infer the applicability of Geant4 in radiation protection for this type of simulation in neutron fields.